A high-toughness conductive polymer organic hydrogel resistant to extreme temperatures and a preparation method thereof

By combining the conductive polypyrum with organic hydrogel, and using physical cross -linking and dual solvents to form a high density structure, the conductive polymer hydrogel loses the problem of mechanical toughness and conductivity at extreme temperature. The conductive polymer organic water gel with extreme temperature and high mechanical strength is implemented, which is suitable for the preparation of flexible strain sensors.

CN115505139BActive Publication Date: 2025-01-28YANSHAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211013692.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-23
Publication Date
2025-01-28
Estimated Expiration
2042-08-23

AI Technical Summary

Technical Problem

The existing conductive polymer hydrogels lose mechanical toughness and conductivity at extreme temperatures, and the preparation process is cumbersome and lack of functionality, which cannot meet the needs of extreme temperature resistance and high mechanical strength.

Method used

The combination of conductive polypyrum and organic hydrogel is used to form a high -density micro -structure with a high density through the physical cross -linked polyethylene glycol network and dual solvents (water and second metalia). Water/two -sectarian solution is soaked, and the high -tough conductive polymer organic water gel resistance to extreme temperature resistance to extreme temperature is generated under synergy.

Benefits of technology

The electrical polymer organic water gel is resistant to extreme temperature characteristics and high mechanical properties. It can not freeze at -90 ° C, maintain flexibility at -45 ° C, work normally at 65 ° C, and has excellent conductive performance and high sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0003811637620000011
    Figure HDA0003811637620000011
  • Figure HDA0003811637620000012
    Figure HDA0003811637620000012
Patent Text Reader

Abstract

The invention discloses a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures and a preparation method thereof. A binary solvent water-dimethyl sulfoxide system and a polymer hydrogel are combined, polyvinyl alcohol is used as a physical network of the conductive polymer organic hydrogel, pyrrole is used as a conductive monomer of the conductive polymer organic hydrogel, both of which are dissolved in a binary solvent of water-dimethyl sulfoxide to prepare a polyvinyl alcohol pregel, and the pregel is immersed in a binary solvent of water-dimethyl sulfoxide of Fe2(SO4)3 to prepare the product. The product does not freeze at -90°C, can maintain good flexibility at -45°C, can work normally at 65°C, has a tensile strength of 0.80MPa-12.0MPa, a fracture strain of 250%-650%, an elastic modulus of 0.85MPa-5.0Mpa, and a toughness of 1.50MJ m ‑3 ‑42.0MJ m ‑3 The present invention is suitable for preparing a highly tough conductive polymer organic hydrogel resistant to extreme temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and relates to a conductive polymer organic hydrogel and a preparation method thereof, and specifically relates to a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures and a preparation method thereof. Background Art

[0002] Hydrogel is a kind of high molecular polymer composed of 3D cross-linked network and water molecules filled in the network, with adjustable physical and chemical properties and biomimetic characteristics. In actual production, flexible electronic devices of single hydrogel are plagued by problems such as poor ductility, low sensitivity and uneven stability, which seriously limits their application and development. Conductive polymer hydrogel has become a strong candidate material for wearable strain sensors due to its flexibility, high tensile strength and biocompatibility. At present, most reports use the co-polymerization method to prepare conductive polymer hydrogels, but the hydrogels prepared by this method are unevenly distributed, have poor gelation effect, and are insufficient in functionality, and cannot be put into large-scale use. Therefore, it is of great application value to study and develop a convenient and efficient preparation method for new conductive polymer hydrogels.

[0003] As an important component of hydrogels, the state and properties of water molecules in the gel network directly affect the physical and chemical properties of such materials. However, under extreme temperatures, due to the evaporation of water molecules in the gel network or the formation of ice crystals, the hydrogel loses its mechanical toughness, becomes hard and brittle, and loses properties such as conductivity and self-healing. In recent years, composite hydrogels with extreme temperature resistance have been developed through methods such as polymer network modification and the introduction of inorganic salts. However, the preparation process of these composite hydrogels is cumbersome, the gel components are complex, and the use of synthetic polymers makes their biocompatibility poor. In addition, most of these composite hydrogels have low toughness and poor mechanical properties, which seriously limits their application range and service life. Therefore, the preparation of high-toughness conductive polymer organic hydrogels with extreme temperature resistance is still a difficult problem to be solved. Summary of the invention

[0004] The present invention aims to provide a high-toughness conductive polymer organic hydrogel with extreme temperature resistance and a preparation method thereof, with the aim of overcoming the shortcomings of existing conductive polymer hydrogels such as poor mechanical properties, complicated preparation process and insufficient functionality, and providing a conductive polymer organic hydrogel with a convenient preparation process, uniform gelation, extreme temperature resistance and high mechanical strength and a preparation method thereof.

[0005] The technical solution of the present invention is as follows:

[0006] The invention discloses an extreme temperature resistant high-toughness conductive polymer organic hydrogel, which is composed of conductive polymer polypyrrole and organic hydrogel. The organic hydrogel is composed of a physically cross-linked polyvinyl alcohol network and a medium, wherein the polyvinyl alcohol content is 5-20wt%, and the medium is a binary solvent, wherein the binary solvent is composed of water and dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the binary solvent is 20-80wt%.

[0007] In this system, the water content and dimethyl sulfoxide control in the binary solvent affect the mechanical properties and extreme temperature resistance of the organic hydrogel. On the one hand, under the strong action of water and dimethyl sulfoxide, the polymer segments begin to arrange in order, the pore structure of the organic hydrogel decreases sharply, and a more highly dense microstructure is formed, thereby improving the mechanical properties; on the other hand, dimethyl sulfoxide binds to the water molecules of the organic hydrogel through strong hydrogen bonds, inhibiting the freezing and evaporation of free water, thereby achieving extreme temperature resistance.

[0008] The present invention also provides a method for preparing a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures, which is carried out in the following steps in sequence:

[0009] (1) dissolving polyvinyl alcohol in a binary solvent of water-dimethyl sulfoxide to form a polyvinyl alcohol solution, adding a pyrrole solution thereto to form a mixed solution, heating the solution to 95° C., and dissolving the solution under magnetic stirring to obtain a light yellow transparent polyvinyl alcohol solution, which is recorded as A;

[0010] (2) transferring A into a mold, and placing the mold alternately in a refrigerator for freezing and thawing at room temperature to obtain polyvinyl alcohol pregel through freeze-thaw cycles to obtain B;

[0011] (3) preparing a binary solvent of water-dimethyl sulfoxide, weighing Fe2(SO4)3 and dissolving it therein to form a water / dimethyl sulfoxide solution with a concentration of 0.5-1.5 mol / L Fe2(SO4)3, to obtain C;

[0012] (4) B is immersed in C to obtain a highly tough conductive polymer organic hydrogel that is resistant to extreme temperatures.

[0013] As a limitation of the preparation method of the present invention:

[0014] (i) In step (1), the mass fraction of dimethyl sulfoxide in the binary solvent is 20-80wt%.

[0015] (ii) In step (1), the mass content of polyvinyl alcohol in the polyvinyl alcohol solution is 5-20wt%, and the mass content of pyrrole in the mixed solution is 2.5-10wt%.

[0016] In this system, the polyvinyl alcohol content and the pyrrole content are more important in the process of forming conductive polymer organic hydrogel. When the polyvinyl alcohol content is too little, there are few cross-linking sites in the organic hydrogel network, the cross-linking density is low and the distribution is extremely uneven, so the mechanical properties are poor; when the polyvinyl alcohol content is too much, hydroxyl side group self-cross-linking occurs between the polyvinyl alcohol molecular chains, the cross-linking degree increases, and the structure becomes dense, thereby hindering the electron mass transfer pathway of the conductive polymer, which manifests as a decrease in conductivity.

[0017] When the pyrrole content is too little, the average distance between the conductive polymers formed by in-situ polymerization increases, and it is difficult for the carriers to migrate continuously and directionally between the polymers, and a continuous and complete conductive path cannot be formed, so the conductive performance is poor; when the pyrrole content is too much, on the one hand, there will be excess pyrrole that cannot undergo oxidation reaction to form polypyrrole, and on the other hand, as the continuous accumulation of polypyrrole reaches the threshold, the reaction rate is inhibited, so the conductive performance reaches a certain balance and no longer increases.

[0018] (III) In step (1), the magnetic stirring rate is 6-9 r / s, and the stirring and dissolving is performed for 1.5-3 h.

[0019] (iv) In step (2), the storage condition in the refrigerator is 7-9 hours at -20°C, and the storage condition at room temperature is 3-5 hours at 25°C, and the number of freeze-thaw cycles is 2-4 times.

[0020] The freeze-thaw process of this step is more critical. The microcrystalline area generated inside the organic hydrogel during the repeated freeze-thaw cycle can serve as a physical cross-linking site, providing an effective energy dissipation pathway, thereby increasing the mechanical properties. In this step, the freezing temperature not only affects the freezing dynamics but also the phase equilibrium between the interfaces. The lower the freezing temperature, the less unfrozen solvent phase there is in the liquid microphase, which helps to increase the crystalline phase. In addition, as the number of freeze-thaw cycles increases, the number of hydrogen bonds in the gel increases and the strength of hydrogen bonds increases, which increases the number of internal cross-linking points. The macroscopic performance is that the crystallinity and thermal stability of the gel are greatly improved.

[0021] (V) In step (4), the soaking time is 5-30 hours.

[0022] The content of Fe2(SO4)3 in the pregel soaking solution is critical. 3+ and SO4 2- Played a synergistic role, on the one hand, due to SO4 2- The Hofmeister effect regulates the aggregation state of the polymer chains, and the polyvinyl alcohol network becomes more dense; on the other hand, pyrrole utilizes Fe 3+The strong oxidizing property of the organic hydrogel is used for in-situ chemical oxidation polymerization to form a polypyrrole conductive network. The synergistic effect of the two greatly improves the mechanical properties of the organic hydrogel.

[0023] In this process, when the concentration of Fe2(SO4)3 is less than 0.5 mol / L, on the one hand, the Fe in the solution can be used for the in-situ oxidation polymerization of pyrrole. 3+ The number of pyrrole decreases, resulting in most of the pyrrole remaining in an unpolymerized monomer state, without forming an effective electron mass transfer channel; on the other hand, SO4 2- The lower concentration leads to a weakening of the Hofmeister effect, which affects the aggregation state of the molecular chain and further affects the toughening degree of the organic hydrogel. When the concentration of Fe2(SO4)3 is greater than 1.5 mol / L, on the one hand, Fe2(SO4)3 is difficult to continue to dissolve and configure into a homogeneous solution, and some precipitation will slowly precipitate during immersion. On the other hand, the mechanical properties and conductive properties of the organic hydrogel reach a state of equilibrium and no longer change significantly with the increase in concentration.

[0024] The present invention has another limitation that in step (3), the mass fraction of dimethyl sulfoxide in the binary solvent is 20-80 wt %.

[0025] The high-toughness conductive polymer organic hydrogel resistant to extreme temperatures provided by the present invention combines a binary solvent water-dimethyl sulfoxide system with extreme temperature resistance and a polymer hydrogel, wherein polyvinyl alcohol is used as a physical network of the conductive polymer organic hydrogel, and pyrrole is used as a conductive monomer of the conductive polymer organic hydrogel, both of which are dissolved in a binary solvent of water-dimethyl sulfoxide to prepare a polyvinyl alcohol pregel, and the polyvinyl alcohol pregel is immersed in a binary solvent of water-dimethyl sulfoxide of Fe2(SO4)3, on the one hand, Fe 3+ The strong oxidizing property of SO4 was used to generate polypyrrole by in-situ chemical oxidation polymerization at the interface, which was used as an electronic conductive medium. 2- The Hofmeister effect optimizes the mechanical properties of conductive polymer organic hydrogels by adjusting the aggregation state of polymer chains to prepare a conductive polymer organic hydrogel that is resistant to extreme temperatures and has high toughness.

[0026] As a whole, the various steps of the above-mentioned preparation method of the present invention are closely related and inseparable.

[0027] After adopting the above technical solution, the beneficial effects achieved by the present invention are as follows:

[0028] 1. The present invention adopts a "one-step immersion method" to prepare a conductive polymer organic hydrogel, which has a simple preparation process, strong controllability, easy controllability, short cycle, and is suitable for industrial promotion and application.

[0029] 2. The present invention uses polyvinyl alcohol and dimethyl sulfoxide as raw materials, which are abundant in source, easy to obtain and low in cost.

[0030] 3. The conductive polymer organic hydrogel prepared by the present invention has good extreme temperature resistance and excellent mechanical properties. The organic hydrogel does not freeze at -90°C, can maintain good flexibility at -45°C, can work normally at 65°C, has a tensile strength of 0.80MPa-12.0MPa, a fracture strain of 250%-650%, an elastic modulus of 0.85MPa-5.0Mpa, and a toughness of 1.50MJ m -3 -42.0MJ m -3 .

[0031] 4. The flexible strain sensor prepared based on the conductive polymer organic hydrogel prepared in the present invention has high sensitivity and excellent conductive properties.

[0032] The invention is suitable for preparing a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0033] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the differential scanning calorimetry characterization diagram of the conductive polymer organic hydrogel and its control group;

[0035] Figure 2 The figure is the mechanical properties of the conductive polymer organic hydrogel and its control group at room temperature;

[0036] Figure 3 This is a graph of the conductivity of the conductive polymer organic hydrogel at high temperatures from 25°C to 65°C;

[0037] Figure 4 Graph showing the tear resistance of conductive polymer organic hydrogel and its control group. DETAILED DESCRIPTION

[0038] In the following examples, the reagents described are all commercially available unless otherwise specified, and the following experimental methods and detection methods are all based on existing experimental methods and detection methods unless otherwise specified.

[0039] The following Examples 1-5 respectively prepare a highly tough conductive polymer organic hydrogel resistant to extreme temperatures, and the reagents used mainly include the following: polyvinyl alcohol, dimethyl sulfoxide, deionized water, pyrrole, and iron sulfate [Fe2(SO4)3].

[0040] Example 1

[0041] This embodiment prepares a high-toughness conductive polymer organic hydrogel that is resistant to extreme temperatures, and the steps are carried out in sequence as follows:

[0042] (1) polyvinyl alcohol was dissolved in a water-dimethyl sulfoxide binary solvent having a dimethyl sulfoxide content of 20 wt % to prepare a polyvinyl alcohol solution having a mass fraction of 5 wt %, and a certain amount of pyrrole solution was added to form a mixed solution so that the mass fraction of pyrrole was 2.5 wt %, and the mixed solution was heated to 95° C. and stirred and dissolved at a magnetic stirring rate of 8 r / s for 1.5 h to obtain a light yellow transparent polyvinyl alcohol solution;

[0043] (2) transferring the solution obtained in step (1) into a mold, and placing the mold alternately in a -20°C refrigerator for 7 hours and at 25°C room temperature for 3 hours, with the number of freeze-thaw cycles being 2 times, to obtain a polyvinyl alcohol pregel through freeze-thaw cycles;

[0044] (3) preparing a binary solution of water / dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 20 wt %; weighing ferric sulfate and dissolving it in the binary solution to a concentration of 0.5 mol / L to form a water / dimethyl sulfoxide solution of Fe2(SO4)3;

[0045] (4) Soaking the polyvinyl alcohol pregel obtained in step (2) in the water / dimethyl sulfoxide solution of Fe2(SO4)3 obtained in step (3) for 5 hours to obtain a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0046] Example 2

[0047] This embodiment prepares a high-toughness conductive polymer organic hydrogel that is resistant to extreme temperatures, and the steps are carried out in sequence as follows:

[0048] (1) polyvinyl alcohol was dissolved in a water-dimethyl sulfoxide binary solvent having a dimethyl sulfoxide content of 33 wt % to prepare a polyvinyl alcohol solution having a mass fraction of 10 wt %, and a certain amount of pyrrole solution was added to form a mixed solution so that the mass fraction of pyrrole was 5 wt %, and the mixed solution was heated to 95° C. and stirred and dissolved at a magnetic stirring rate of 6 r / s for 1.5 h to obtain a light yellow transparent polyvinyl alcohol solution;

[0049] (2) transferring the solution obtained in step (1) into a mold, and placing the mold alternately in a -20°C refrigerator for 8 h and at 25°C room temperature for 4 h, with the freeze-thaw cycle number being 3 times, to obtain a polyvinyl alcohol pregel through freeze-thaw cycles;

[0050] (3) preparing a binary solution of water / dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 33 wt %; weighing ferric sulfate and dissolving it in the binary solution to a concentration of 1 mol / L to form a water / dimethyl sulfoxide solution of Fe2(SO4)3;

[0051] (4) Soaking the polyvinyl alcohol pregel obtained in step (2) in the water / dimethyl sulfoxide solution of Fe2(SO4)3 obtained in step (3) for 5 hours to obtain a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0052] Example 3

[0053] This embodiment prepares a high-toughness conductive polymer organic hydrogel that is resistant to extreme temperatures, and the steps are carried out in sequence as follows:

[0054] (1) polyvinyl alcohol is dissolved in a water-dimethyl sulfoxide binary solvent having a dimethyl sulfoxide content of 50 wt % to prepare a polyvinyl alcohol solution having a mass fraction of 15 wt %, a certain amount of pyrrole solution is added to form a mixed solution, wherein the mass fraction of pyrrole in the mixed solution is 7.5 wt %, the mixed solution is heated to 95° C., and stirred and dissolved at a magnetic stirring rate of 9 r / s for 2 h to obtain a light yellow transparent polyvinyl alcohol solution;

[0055] (2) transferring the solution obtained in step (1) into a mold, and placing the mold alternately in a -20°C refrigerator for 8 h and at 25°C room temperature for 4 h, with the freeze-thaw cycle number being 3 times, to obtain a polyvinyl alcohol pregel through freeze-thaw cycles;

[0056] (3) preparing a binary solution of water / dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 50 wt %; weighing ferric sulfate and dissolving it in the binary solution to a concentration of 1 mol / L to form a water / dimethyl sulfoxide solution of Fe2(SO4)3;

[0057] (4) Soaking the polyvinyl alcohol pregel obtained in step (2) in the water / dimethyl sulfoxide solution of Fe2(SO4)3 obtained in step (3) for 20 hours to obtain a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0058] Example 4

[0059] This embodiment prepares a high-toughness conductive polymer organic hydrogel that is resistant to extreme temperatures, and the steps are carried out in sequence as follows:

[0060] (1) polyvinyl alcohol is dissolved in a water-dimethyl sulfoxide binary solvent having a dimethyl sulfoxide content of 66 wt % to prepare a polyvinyl alcohol solution having a mass fraction of 15 wt %, a certain amount of pyrrole solution is added to form a mixed solution, wherein the mass fraction of pyrrole in the mixed solution is 10 wt %, the mixed solution is heated to 95° C., and stirred and dissolved at a magnetic stirring rate of 7 r / s for 2 h to obtain a light yellow transparent polyvinyl alcohol solution;

[0061] (2) transferring the solution obtained in step (1) into a mold, and placing the mold alternately in a -20°C refrigerator for 9 hours and at 25°C room temperature for 5 hours, with the number of freeze-thaw cycles being 4 times, and obtaining a polyvinyl alcohol pregel through freeze-thaw cycles;

[0062] (3) preparing a binary solution of water / dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 66 wt %; weighing ferric sulfate and dissolving it in the binary solution to a concentration of 1.5 mol / L to form a water / dimethyl sulfoxide solution of Fe2(SO4)3;

[0063] (4) Soaking the polyvinyl alcohol pregel obtained in step (2) in the water / dimethyl sulfoxide solution of Fe2(SO4)3 obtained in step (3) for 20 hours to obtain a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0064] Example 5

[0065] This embodiment prepares a high-toughness conductive polymer organic hydrogel that is resistant to extreme temperatures, and the steps are carried out in sequence as follows:

[0066] (1) polyvinyl alcohol is dissolved in a water-dimethyl sulfoxide binary solvent having a dimethyl sulfoxide content of 80 wt % to prepare a polyvinyl alcohol solution having a mass fraction of 20 wt %, a certain amount of pyrrole solution is added to form a mixed solution, the mass fraction of pyrrole in the mixed solution is 10 wt %, the mixed solution is heated to 95° C., and stirred and dissolved at a magnetic stirring rate of 8 r / s for 3 h to obtain a light yellow transparent polyvinyl alcohol solution;

[0067] (2) transferring the solution obtained in step (1) into a mold, and placing the mold alternately in a -20°C refrigerator for 9 hours and at 25°C room temperature for 5 hours, with the number of freeze-thaw cycles being 4 times, and obtaining a polyvinyl alcohol pregel through freeze-thaw cycles;

[0068] (3) preparing a binary solution of water / dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the mixed solution is 80 wt %; weighing ferric sulfate and dissolving it in the binary solution to a concentration of 1.5 mol / L to form a water / dimethyl sulfoxide solution of Fe2(SO4)3;

[0069] (4) Soaking the polyvinyl alcohol pregel obtained in step (2) in the water / dimethyl sulfoxide solution of Fe2(SO4)3 obtained in step (3) for 30 hours to obtain a high-toughness conductive polymer organic hydrogel with extreme temperature resistance.

[0070] Example 6 Performance Test

[0071] Some performance tests were performed on the materials prepared in Examples 1 to 5. For specific results, see Figure 1-Figure 4 shown.

[0072] Figure 1 The conductive polymer organic hydrogel was subjected to differential scanning calorimetry analysis to explore the glass transition temperature of the organic hydrogel at low temperatures of 20°C to -90°C. As can be seen from the figure, an exothermic peak was observed at -20.3°C for the polyvinyl alcohol hydrogel without the introduction of dimethyl sulfoxide (the product prepared by Group A in Comparative Example 1), indicating that the free water molecules in the polyvinyl alcohol network were frozen to form ice crystals. However, no exothermic peak was observed for the organic hydrogel introduced with dimethyl sulfoxide, indicating that the water molecules in the organic hydrogel will not freeze at -90°C. This is because dimethyl sulfoxide can combine with water molecules to form hydrogen bonds, inhibiting the decomposition of free water, thereby significantly changing the water state in the organic hydrogel, so that the conductive polymer organic hydrogel can work normally at extremely low temperatures.

[0073] Figure 2 The figure is a graph of the mechanical properties of the conductive polymer organic hydrogel and its control group (the product prepared in the comparative example) at room temperature. It can be seen from the figure that at room temperature, the tensile strength of the organic hydrogel prepared by the method of the present invention can still be as high as 8MPa, and the fracture strain can reach 550%, while the tensile strength and fracture strain of the untreated polyvinyl alcohol hydrogel are only 0.02MPa and 270%, respectively. This is because after being immersed in the water / dimethyl sulfoxide solution of Fe2(SO4)3, on the one hand, due to the SO4 2- The Hofmeister effect regulates the aggregation state of the polymer chains, and the polyvinyl alcohol network becomes more dense; on the other hand, pyrrole utilizes Fe 3+ The strong oxidizing property of dimethyl sulfoxide is used to generate a polypyrrole conductive network through in-situ chemical oxidation polymerization at the interface. The synergistic effect of the two greatly improves the mechanical properties of the organic hydrogel. In addition, as dimethyl sulfoxide enters the polyvinyl alcohol network, the hydrogen bonding between the two helps to improve the mechanical strength of the polymer network, gradually increasing its tensile strength and elongation at break, expanding the working range of the conductive polymer organic hydrogel and improving its working durability.

[0074] Figure 3This is a performance characterization diagram of conductive polymer organic hydrogel under extreme temperature. When the ambient temperature rises to 65°C, the organic hydrogel can still work normally and as the ambient temperature rises, the conductivity of the organic hydrogel increases to 0.949S / m, showing good conductive properties. The results show that the introduction of dimethyl sulfoxide greatly broadens the working temperature range, greatly improving its working life and application range.

[0075] Figure 4 The tear resistance of the conductive polymer organic hydrogel and its control group is characterized. From the experimental results, it can be seen that the tear force of the organic hydrogel treated by the method of the present invention is as high as 10.3N, and the tear energy can reach 560.8kJ / m 2 , indicating that it has high toughness and excellent tear resistance, can be applied to various complex working environments and maintain good working stability.

[0076] Example 7 Comparative Example 1

[0077] Traditional hydrogels are prone to dehydration and drying under high temperature conditions, and are prone to freezing and failure under low temperature conditions, losing many functions, such as elasticity, conductivity, transparency, and adaptability. This example conducted the following experiment by performing differential scanning calorimetry analysis on the prepared product to compare the effect of the introduction of dimethyl sulfoxide on the low temperature resistance of the conductive polymer organic hydrogel:

[0078] Group a (P): The hydrogel prepared in this group was prepared in a similar process to that in Example 1, except that the binary solvent in step (1) was water and no pyrrole solution was introduced, and the soaking step in step (4) was omitted. Figure 1 It can be seen that without the introduction of dimethyl sulfoxide, an exothermic peak was observed at -20.3 °C, indicating that the free water in the cross-linked network of polyvinyl alcohol was frozen into ice crystals.

[0079] Group b (PDP): The organic hydrogel prepared in this group was prepared in a similar process to that in Example 1, except that the binary solvents in steps (1) and (3) were both water and no pyrrole solution was introduced. Figure 1 It is found that when dimethyl sulfoxide is introduced, no exothermic peak appears in the differential scanning calorimetry data of the organohydrogel.

[0080] Group c (PDFe@PPy-H): Conductive polymer organic hydrogel prepared in this group was obtained according to the preparation process described in Example 1. Figure 1 It can be seen that the introduction of dimethyl sulfoxide causes the exothermic peak of the conductive polymer organic hydrogel to shift to a lower temperature, indicating that the freezing point is greatly reduced.

[0081] Example 8 Comparative Example 2

[0082] The mechanical properties of traditional hydrogels are poor, which seriously limits their application in actual production and life. In this example, the following experiments were conducted to compare the effects of the introduction of dimethyl sulfoxide, polypyrrole and Hofmeister effect on the mechanical properties of conductive polymer organic hydrogels:

[0083] Group A: The hydrogel prepared in this group was prepared in the same way as in Example 1 without any experimental treatment. Figure 2 It can be seen that the mechanical properties of polyvinyl alcohol hydrogel are extremely poor because only partial hydrogen bonds are formed inside the hydrogel through freeze-thaw cycles.

[0084] Group B: The organic hydrogel prepared in this group lacks the introduction of polypyrrole and Hofmeister effect compared with the preparation process of Example 1. Figure 2 It can be seen that since dimethyl sulfoxide is a strong hydrogen bond acceptor, it preferentially forms hydrogen bonds with polyvinyl alcohol and inhibits the formation of hydrogen bonds within / between molecular chains, allowing it to maintain an extended conformation and uniform arrangement, forming a more highly dense microstructure, thereby improving the mechanical properties.

[0085] Group C: The hydrogel prepared in this group, the preparation process is compared with Example 1, lacks the introduction of dimethyl sulfoxide and polypyrrole, the results are Figure 2 It can be seen that under the action of the Hofmeister effect, polyvinyl alcohol hydrogel changes the internal network structure of the hydrogel by regulating the aggregation state of the polymer chains through ions, thereby improving the mechanical properties of the hydrogel.

[0086] Group d: The organic hydrogel prepared in this group lacks the introduction of polypyrrole compared with the preparation process of Example 1. Figure 2 It can be seen that under the synergistic effect of the strong hydrogen bonds of dimethyl sulfoxide and the Hofmeister effect, the internal pores of the organic hydrogel are drastically reduced and the microstructure is further densified, resulting in extensive improvement in the mechanical properties.

[0087] Group e: Conductive polymer organic hydrogel prepared by this group was obtained according to the preparation process described in Example 1. Figure 2 It can be seen that the interaction between polypyrroles and the hydrogen bonding between polypyrrole and polyvinyl alcohol molecular chains, based on the synergistic effect of the strong hydrogen bonding of dimethyl sulfoxide and the Hofmeister effect, play a certain role in improving the overall mechanical action of the conductive polymer organic hydrogel, but the effect is small.

[0088] The products prepared by the above-mentioned groups a to e were subjected to relevant performance tests, as shown in the table below.

[0089]

[0090] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a highly tough conductive polymer organic hydrogel resistant to extreme temperatures, comprising the following steps: (1) polyvinyl alcohol is dissolved in a binary solvent of water-dimethyl sulfoxide to form a polyvinyl alcohol solution, wherein the mass fraction of dimethyl sulfoxide in the binary solvent is 20-80 wt%, and the mass content of polyvinyl alcohol in the polyvinyl alcohol solution is 5-20 wt%. A pyrrole solution is added thereto to form a mixed solution, and the mixed solution is heated to 95° C., wherein the mass content of pyrrole in the mixed solution is 2.5-10 wt%. The mixed solution is dissolved under magnetic stirring to obtain a light yellow transparent polyvinyl alcohol solution, which is recorded as A; (2) Transfer A into a mold, and alternately place the mold in a refrigerator to freeze and thaw at room temperature to obtain polyvinyl alcohol pregel through freeze-thaw cycles to obtain B; (3) preparing a binary solvent of water-dimethyl sulfoxide, wherein the mass fraction of dimethyl sulfoxide in the binary solvent is 20-80wt%, weighing Fe2(SO4)3 and dissolving it therein, A water-dimethyl sulfoxide solution with a concentration of 0.5-1.5 mol / L Fe2(SO4)3 is formed to obtain C; (4) Soak B in C to obtain a highly tough conductive polymer organic hydrogel that is resistant to extreme temperatures.

2. The method for preparing a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures according to claim 1, characterized in that: In step (1), the magnetic stirring rate is 6-9 r / s, and the stirring and dissolving is performed for 1.5-3 h.

3. The method for preparing a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures according to claim 1, characterized in that: In step (2), the storage condition in the refrigerator is 7-9 h in a -20°C refrigerator, and the storage condition at room temperature is 3-5 h at 25°C. The number of freeze-thaw cycles is 2-4 times.

4. The method for preparing a high-toughness conductive polymer organic hydrogel resistant to extreme temperatures according to claim 1, characterized in that: In step (4), the soaking time is 5-30 h.

Citation Information

Patent Citations

  • Composite hydrogel, preparation method and application thereof

    CN109251449A